Effects of Classical Music, Natural and Murottal Music on Fetal Well-Being - Rahayu ` Sumaningsih; Teta Puji Rahayu; Budi Joko Santosa (Humanistic Network for Science and Technology (HNST), 2020)
Music affects to human psychology, provides a sense of security, comfort and fun. Classical, natural and murottal music has a tone, rhythm, speed, gentle meter capable of stimulating alpha waves, calmness, and relaxation, beneficial to the well-being of the fetus. The purpose of this study is to describe classical, natural and murotal music on fetal well-being. This Quasi-Experiment Research with pretest-posttest design. A sample of 40 individuals was divided into 4 groups of mothers. The independent variable is classical music, natural, murotal and without music. The dependent variable is fetal well-being. The mean values before and after the intervention naturally were calculated. The results of fetal well-being based on the fetal heart rate of the classical music group before treatment there were 10% of fetuses experiencing mild aspysia after treatment of the fetus experiencing 0% aspysia. Natural and Murottal Music Group before and after treatment 100% normal fetal heart rate, group without music, before and after treatment 50% of fetuses experience Mild Aspysia. Fetal wellbeing results are based on Apgar Score, the Classical Music group after listening to classical music 10% experienced mild Aspysia. Natural Music Group and Murottal after listening to natural music and murottal 100% of babies under normal circumstances. The group without music after birth 50% of babies experience mild Aspysia. Conclusion, classical music overcomes mild asphyxia based on fetal heart rate, natural and murrotal music effectively maintains fetal well-being until birth. Keywords: classical music; natural music; murottal; fetal well-being